F1FO ATP Synthase Is Expressed at the Surface of Embryonic Rat Heart‐Derived H9c2 Cells and Is Affected by Cardiac‐Like Differentiation. Issue 2 (February 2016) - Comelli, Marina; Domenis, Rossana; Buso, Alessia; Mavelli, Irene
ABSTRACT: Taking advantage from the peculiar features of the embryonic rat heart‐derived myoblast cell line H9c2, the present study is the first to provide evidence for the expression of F1 FO ATP synthase and of ATPase Inhibitory Factor 1 (IF1 ) on the surface of cells of cardiac origin, together documenting that they were affected through cardiac‐like differentiation. Subunits of both the catalytic F1 sector of the complex (ATP synthase‐β) and of the peripheral stalk, responsible for the correct F1 ‐FO assembly/coupling, (OSCP, b, F6) were detected by immunofluorescence, together with IF1 . The expression of ATP synthase‐β, ATP synthase‐ b and F6 were similar for parental and differentiated H9c2, while the levels of OSCP increased noticeably in differentiated cells, where the results of in situ Proximity Ligation Assay were consistent with OSCP interaction within ecto‐F1 FO complexes. An opposite trend was shown by IF1 whose ectopic expression appeared greater in the parental H9c2. Here, evidence for the IF1 interaction with ecto‐F1 FO complexes was provided. Functional analyses corroborate both sets of data. i) An F1 FO ATP synthase contribution to the exATP production by differentiated cells suggests an augmented expression of holo‐F1 FO ATP synthase on plasma membrane, in line with the increase of OSCP expression and interaction considered as a requirement for favoring the F1 ‐FO coupling. ii) The absence of exATP generation by the enzyme, and the finding that exATP hydrolysis was largely oligomycin‐insensitive, are in line in parental cells with the deficit of OSCP and suggest the occurrence of sub‐assemblies together evoking more regulation by IF1 . J. Cell. Biochem. 9999: 1–13, 2015. © 2015 Wiley Periodicals, Inc. J. Cell. Biochem. 117: 470–482, 2016. © 2015 Wiley Periodicals, Inc.